Financing for development : building on Monterrey (UN New YorkUS, 2002)
Offers a comprehensive view of the Monterrey Conference. Examines the landmark global agreement between developed and developing countries, in which both recognise their responsibilites in key areas such as trade, aid, debt relief and institution builidng. Presents a breakthrough on the question of official development assistance. Reiterates that poor and economically distressed people need not be objects of pity and charity; rather, they should be regarded as untapped reservoirs of initiative, and should be welcomed as partners in the development process.
Includes the text of the Monterrey Consensus.